Addressing Social Exclusion: Analyses from South Asia and Southern Africa - Johnston, Heidi Bart (Journal of Health, Population and Nutrition, 2009)
doi: 10.3329/jhpn.v27i4.3386 J Health Popul Nutr 2009 Aug;27(4):423-425